2015
DOI: 10.1177/016146811511701307
|View full text |Cite
|
Sign up to set email alerts
|

How Positioning Shapes Opportunities for Student Agency in Schools

Abstract: This chapter shows how student positioning by adults shapes opportunities for students to develop collective systemic agency. Collective systemic agency refers to the capacity to organize others, participate in discussions, develop a systemic analysis, and take action in complex institutions, such as schools. This repertoire can be cultivated by encouraging students to ask critical questions about their educational experiences and to uncover evidence about how policy affects people. In observing this process t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Repositioning involves strategies to increase the perceived legitimacy of student interventions in policy conversations. Such strategies may include students claiming subject matter expertise on their own experience (Conner & Rosen, 2015b; York & Kirshner, 2015). Reframing, drawing on Goffman’s (1974) description of frames as “schemata of interpretation” that allow people to “locate, perceive, identify, and label” phenomena (p. 21), involves strategies where students use their unique position to shift policy discourse in advantageous ways by disrupting preexisting interpretive schemes.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Repositioning involves strategies to increase the perceived legitimacy of student interventions in policy conversations. Such strategies may include students claiming subject matter expertise on their own experience (Conner & Rosen, 2015b; York & Kirshner, 2015). Reframing, drawing on Goffman’s (1974) description of frames as “schemata of interpretation” that allow people to “locate, perceive, identify, and label” phenomena (p. 21), involves strategies where students use their unique position to shift policy discourse in advantageous ways by disrupting preexisting interpretive schemes.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…We found that setting can dictate focus. Although examples exist of student voice practices set in the classroom that focus on effecting school or even district policy (Cohen et al, 2020; York & Kirshner, 2015), most of the examples of student voice practices within the literature and shared by students, teachers, and school administrators showed alignment between setting and focus; that is, classroom student voice practices focused on classroom policy and practice, while school student voice practices focused on school policy and practice.…”
Section: Resultsmentioning
confidence: 99%
“…Critique of student voice scholarship has increasingly focused on how student voice practices may be co-opted to reinforce oppression rather than to focus on social justice (Balakrishnan & Claiborne, 2017; Holquist & Walls, 2021a; McNae & Cowie, 2017; Mayes et al, 2016, 2021; Bertrand & Rodela, 2018; York & Kirshner, 2015; Robinson & Taylor, 2013; Rodela & Bertrand, 2021). For example, Lac and Cumings Mansfield (2018) identified three levers for effective student voice in educational leadership: (a) positioning of students as change agents, (b) school administrators who support the centering of student voice, and (c) the actual creation of opportunities for student voice to occur.…”
Section: Student Voice As Critical Distributed Leadershipmentioning
confidence: 99%
“…Another approach to broader change through YPAR involves repositioning youth so that they have more power and influence (Bertrand, 2018;Ozer & Wright, 2012;Rodríguez & Brown, 2009). This was shown to be the case in a study of student action research projects facilitated by two teachers in two different schools (York & Kirshner, 2015). One of these teachers repeatedly referred to her students as researchers, while administrators at the school positioned the students as valuable contributors to school policy.…”
Section: Policy-and Practice-level Transformative Potentialmentioning
confidence: 99%